Philosophcal Methods of Treating Mental Patients With the Local Wisdom of Wat Pa Don Puea, Kham Tao Subdistrict, Kantharawichai District Mahasarakham Province - Silavatpaphakorn, PhraKru; Bhavanabodhikun, Phrakhru; Leeka, Jaras; Kamolsil, Uthai; Katasaro (Saengyoi), PhramahaPaphon; Phengwiphat, Phonphao (Journal of Graduate MCU KhonKaen Campus, 2022)
The objectives of this research are 1) to study the problems of the mental patients of the Wat pa don puea, 2) to study the folk wisdom for the treatment of the mentally patients, 3) to analyze the philosophcal methods of treating mental patients with the local wisdom of wat pa don puea, kham tao subdistrict, kantharawichai district mahasarakham province, It is a qualitative research. Study information from the Tripitaka, documents and related research. There were 30 key informants / person who analyzed the data in a descriptive method based on the inductive method. The research results were as follows: 1. Problems of mental patients arise from the main causes which are Family problems Economic problem And social and environmental problems 2) Folk wisdom in treating mental patients can be divided into 1) physical therapy, there are 3methods: herbal oil treatment, and blowing 2) psychological treatment, there are 3 methods: Mo Lam Song, Mortham and Brahmin. 3) There are 2 methods of treating mental patients with the local wisdom of Wat Pa Don Nude, namely physical therapy. By drinking holy water And the holy bathing How to stay mentally With prayer And mental prayer meditation When analyzing according to definition 5, it was found that the disease caused by peaches, which was defined as can be treated with medicine and herbs. But the disease arising from the mind, the definition, the karma, the definition, and the Dharma need to use the medicine in the treatment.